1984
DOI: 10.1159/000137967
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Application of &alpha;<sub>1</sub>and &alpha;<sub>2</sub>-Adrenoceptor Agonists and Antagonists into the Ventromedial Hypothalamus on the Sodium and Potassium Renal Excretion

Abstract: The effects of sodium and potassium excretion after intrahypothalamic administration of two α-adrenoceptor agonists and the effect of α-adrenoceptor antagonists were studied in groups of rats. Prazosin was equally effective at blocking the natriuretic and kaliuretic responses to the α1-adrenoceptor agonist phenylephrine and the mixed α12-adrenoceptor agonist noradrenaline, while yohimbine which acts preferentially on α2-adrenoceptors was effective in potentiating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…The autoradiographic localization of [3]clonidine binding to non-adrenergic sites was similar to, but distinct from, α 2 -adrenergic receptors in human brain (31). Prazosin is effective in blocking the natriuretic and kaliuretic response to the α 1 -adrenoceptor agonist phenylephrine (32). The present study shows that injection of prazosin into the MSA did not modify the inhibitory responses induced by ANGII injected into the 3rdV on sodium, potassium and water excretion.…”
Section: Discussionsupporting
confidence: 57%
“…The autoradiographic localization of [3]clonidine binding to non-adrenergic sites was similar to, but distinct from, α 2 -adrenergic receptors in human brain (31). Prazosin is effective in blocking the natriuretic and kaliuretic response to the α 1 -adrenoceptor agonist phenylephrine (32). The present study shows that injection of prazosin into the MSA did not modify the inhibitory responses induced by ANGII injected into the 3rdV on sodium, potassium and water excretion.…”
Section: Discussionsupporting
confidence: 57%
“…In line with this working model, brain slice electrophysiological recordings of NE-responsive PVN neurons revealed that the excitatory effect of NE is mimicked by α 1 agonist phenylephrine (PHE), while the inhibitory effect of NE is mimicked by α 2 agonist clonidine (Wellman et al, 1993). Similar co-localization and antagonistic actions are observed in other brain regions, including NTS, DMV and VMH, suggesting that this mutual antagonistic mode of action of α 1 and α 2 -AR is generalized across different brain regions (Young and Kuhar, 1980;Saad et al, 1984;Feldman and Felder, 1989). Antagonistic action between α 1 and α 2 receptors on feeding is versatile and tightly regulated.…”
Section: Hypothalamic α-Adrenergic Receptors In Cardiometabolic Regulationmentioning
confidence: 82%
“…The potential contributions of the central nervous system and kidneys in these models of chronic stress hypertension are suggested by studies of acute environmental stress. Acute exposure to air jet stress leads to antinatriuresis and an increase in renal sympathetic nerve activity that is much greater in nephrine into the ventromedial hypothalamus, lateral hypothalamus, septal area, or 3rd cerebral ventricle of conscious rats; this natriuresis is prevented by ai-adrenoceptor antagonists and is potentiated by a 2 -adrenoceptor antagonists (Camargo et al, 1976;Morris et al, 1977;Pillar et al, 1977;Saad et al, 1984). In contrast, an antinatriuresis follows the injection of isoproterenol into the lateral hypothalamus, septal area, or 3rd cerebral ventricle; this antinatriuresis is abolished by ft, 2 -or ft-, but not ft-adrenoceptor antagonists (Morris et al, 1977;Pillar et al, 1977;Camargo et al, 1979).…”
mentioning
confidence: 99%